Joint trajectories of physical activity, health, and income before and after statutory retirement: A 22-year follow-up - Tea Lallukka; Petteri Kolmonen; Ossi Rahkonen; Eero Lahelma; Jouni Lahti (PLoS ONE, 2025)
Background Health behaviors, health, and income change during aging. However, no previous studies have examined, how they develop together over the transition to statutory retirement. We aimed to examine their joint development and to identify the determinants of any distinct trajectories. Methods We studied former employees of the City of Helsinki, Finland, who transitioned to full statutory retirement between 2000 and 2022 (n = 5209, 80% women). We examined five repeated questionnaire surveys to identify any joint developmental patterns in the key indicators of healthy aging and well-being—leisure-time physical activity, health measured by general health perceptions, and household income, over a follow-up of 22 years. We used joint group-based trajectory analysis to identify latent developmental groups. The social and health-related determinants of trajectory group membership are reported as average marginal effects. Results We found four distinct joint trajectory groups. Group 1 (22.6%) had consistently poor general health perceptions, less physical activity than the recommended amount, and low income. In Group 2 (34.2%), general health perceptions were first good but then declined, and income was low but slightly increasing. Group 3 (12.3%) had good general health perceptions, a very high level of physical activity, but fluctuating income. In Group 4 (30.9%), general health perceptions were first good but then declined, physical activity was at the recommended level, and income was sharply increasing. People with obesity had a 22 percentage-point (21–24) higher predicted probability of belonging to Group 1 than people with normal weight. They were also more likely to report low education and more physician-diagnosed chronic diseases and mental disorders. Conclusions We identified distinct trajectories in physical activity, general health perceptions, and income over a follow-up of over 20 years. The majority of those who had transitioned to statutory retirement had good general health perceptions but varying levels of physical activity and income. As not all those with a low income had a low level of physical activity or poor general health perceptions, public health interventions should target distinct groups with the most adverse risk factor profiles, to narrow health inequalities during aging.